2011
DOI: 10.1128/aem.00611-11
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Distribution of Secondary Metabolite Genes in the Marine Actinomycete Salinispora arenicola

Abstract: The molecular fingerprinting technique terminal-restriction fragment length polymorphism (T-RFLP) was used in combination with sequence-based approaches to evaluate the geographic distribution of secondary metabolite biosynthetic genes in strains of the marine actinomycete Salinispora arenicola. This study targeted ketosynthase (KS) domains from type I polyketide synthase (PKS) genes and revealed four distinct clusters, the largest of which was comprised of strains from all six global locations sampled. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…In general, KS or C domains derived from the same pathway often share ≥90% amino acid sequence identity. In cases where a query sequence shares this level of identity with a reference sequence, it can be predicted that the pathway from which the sequence was derived has a high probability of producing compounds in the same structural class, as has been demonstrated previously (Edlund et al, 2011; Gontang et al, 2010). For domains that share <90% identity to the top NaPDoS match, an NCBI BLAST search is highly recommended as the NaPDoS database is not comprehensive.…”
Section: Napdosmentioning
confidence: 68%
See 1 more Smart Citation
“…In general, KS or C domains derived from the same pathway often share ≥90% amino acid sequence identity. In cases where a query sequence shares this level of identity with a reference sequence, it can be predicted that the pathway from which the sequence was derived has a high probability of producing compounds in the same structural class, as has been demonstrated previously (Edlund et al, 2011; Gontang et al, 2010). For domains that share <90% identity to the top NaPDoS match, an NCBI BLAST search is highly recommended as the NaPDoS database is not comprehensive.…”
Section: Napdosmentioning
confidence: 68%
“…KS domains are the most conserved and form an essential part of each PKS gene cluster. These domains have been used to fingerprint PKS genes from individual strains (Edlund, Loesgen, Fenical, & Jensen, 2011) and environmental DNA (Wawrik et al, 2007). KS phylogeny has even been used to predict secondary metabolite diversity (Foerstner, Doerks, Creevey, Doerks, & Bork, 2008; Metsa-Ketela et al, 1999), structures (Freel, Nam, Fenical, & Jensen, 2011; Gontang, Gaudencio, Fenical, & Jensen, 2010), and the evolutionary processes that generate new structural diversity (Freel et al, 2011)…”
Section: Introductionmentioning
confidence: 99%
“…Biogeographical studies have revealed that S. tropica is restricted to the Caribbean, “ S. pacifica ” occurs worldwide except for the Caribbean, and S. arenicola is broadly distributed and co-occurs with both species (Jensen and Mafnas 2006; Freel et al 2012). Previous studies have also revealed relationships between Salinispora taxonomy and secondary metabolite production (Jensen et al 2007) and correlations between where the strains were derived and the biosynthetic genes they maintain (Edlund et al 2011). These results suggest that culturing new Salinsipora species or known species from new locations is a potentially productive approach to natural product discovery.…”
Section: Introductionmentioning
confidence: 99%
“…KSs are the most conserved domains and found as essential part of each PKS gene cluster as they have been used to identify PKS genes from individual bacterial strains [28] and environmental DNA [29] . Each catalytic site is encoded on a distinct protein by type II PKSs, which also called iterative type of PKS.…”
Section: Resultsmentioning
confidence: 99%